2021
DOI: 10.1158/1538-7445.am2021-ct191
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT191: A window-of-opportunity study with atezolizumab and the oncolytic virus pelareorep in early breast cancer (AWARE-1)

Abstract: Background: A previous phase 2 study in metastatic breast cancer demonstrated a statistically significant improvement in overall survival (OS) in patients treated with pelareorep (pela), an intravenously delivered immuno-oncolytic reovirus, given in combination with paclitaxel (PTX) versus PTX alone [1]. We hypothesized that the OS benefit from pela + PTX may be attributed to an adaptive T cell response triggered by pela. To examine if pela can mediate the priming of an anti-tumor immune response, and the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For this experiment, the clinical-grade formulation of Reo, named pelareorep (Pela in graphs), was used. Pelareorep is currently under investigation in multiple clinical trials as part of combinatorial approaches, including T cell–based immunotherapy, and has shown promising results ( 41, 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…For this experiment, the clinical-grade formulation of Reo, named pelareorep (Pela in graphs), was used. Pelareorep is currently under investigation in multiple clinical trials as part of combinatorial approaches, including T cell–based immunotherapy, and has shown promising results ( 41, 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the early termination of phase II trial exploring pelareorep and pembrolizumab, the interim results from phase I/II trial evaluating the combination of pelareorep and anti-PD-L1 ICI atezolizumab (Eudra-CT Number: 2020-003996-16) for the treatment of advanced gastrointestinal cancers revealed that the combination therapy administered to 3 out of 3 patients with locally advanced/metastatic unresectable pancreatic ductal adenocarcinoma led to partial response at week 16 after the treatment with no safety signals. Similarly, interim results from the phase I trial evaluating the combination of pelareorep and atezolizumab in patients with early breast cancer (NCT04102618) that are hormone receptor-positive and HER2-negative were promising ( 107 ). The study evaluated CelTIL score, a metric that quantitates changes in tumor cellularity and TIL with higher score correlating to favorable therapeutic responses, and met the primary endpoint of the trial when greater than 30% increase in CelTIL score was achieved in 40% of the patients receiving pelareorep in absence of atezolizumab and 60% in the combination therapy arm.…”
Section: Current Clinical Trial Landscapementioning
confidence: 99%
“…New emerging technologies are on the horizon for the treatment of breast cancer, including immuno-oncolytic virus drugs, histone deacetylase inhibitors, and novel combination therapies [9][10][11]. In this review, we will discuss the most novel breast cancer treatments for HER2-positive, HER2-negative, and triple-negative breast cancers, and the possibilities implicated in combinatorial therapy for the future of breast cancer medicine (Table 1).…”
Section: Introductionmentioning
confidence: 99%